STUDI KASUS: PEMERIKSAAN KADAR ALBUMIN DAN GLUKOSA URINE PADA ASUHAN KEHAMILAN Ny. I DI WILAYAH KERJA PUSKESMAS AIR BESAR KOTA AMBON - Wa Ode Rahmawati (Poltekkes Kemenkes Maluku, 2023)
Pregnancy checks are very important for all pregnant women to determine fetal growth and maternal health, including detecting protein and glucose levels in the urine. Examination of urine albumin is a parameter of routine urine examination needed to help make a diagnosis. It is necessary to detect protein levels in the urine to diagnose preeclampsia because it can cause problems in pregnancy and childbirth and can even cause pain, as well as Diabetes Mellitus (DM). Complications of DM in pregnancy affect the mother and baby, namely premature birth, large babies, hypoglycemia, infant death in the womb, risk of pre-eclampsia, cesarean section (planned or emergency) and infant shoulder dystocia so it is also necessary to check urine glucose levels. This case study illustrates the indications for urine albumin and glucose examination where the mother is 42 years old, third trimester of pregnancy, complains of headaches and feels dizzy, current weight is 73 kg, last visit's weight was 69 kg. Blood pressure 140/90 mm Hg, there is edema in the leg area. The author conducted a laboratory examination and found that the urine albumin value was +1 while the urine glucose level was negative. Diagnosed with Mrs. I with mild preeclampsia. Midwifery care that is carried out focuses on overcoming the discomfort experienced by the mother and mild preeclampsia. Care was carried out for 4 visits with an interval of 1 week. On April 28, 2023 the results of the weight examination decreased 130/80 mmHg, the headaches were no longer felt, the urine albumin and glucose were negative. Early detection by carrying out a comprehensive examination from health workers including laboratory tests is needed to achieve the health status of pregnant women and family support so that the mother and fetus remain healthy during pregnancy.